Red Betel Leaf (Piper crocatum) Tea Efication in Overcoming Leucorhea - Sukini, Tuti; Arfiana; Yuniyanti, Bekti; Munayarokh; Nikmawati, Nuril (International Journal of Psychosocial Rehabilitation, 2020)
Background: A woman’s reproductive health cannot be separated from her intimate organ. If not carefully maintained, it can disturb the balance; one symptom of the disruption is leucorrhea. More than 75% of adult women have experienced leucorrhea throughout their life cycle, and 45% of them may experience leukorrhea twice or more. According to the WHO, 65% of the population of developed countries and 80% of the population of developing countries have been using herbal medicine as traditional medicine. WHO’s support for the concept of returning to nature is proved by the existence of the recommendation of using traditional medicine, including herbs. Red betel leaf (Piper crocatum) is one of the traditional ingredients that has been long used. Purpose: The purpose of this research is to analyze the efficacy of Red Betel Leaf (Piper crocatum) tea to resolve the symptoms of leuchorea. Methods: This research is quantitative research with a quasi-experimental study design. The design used is a two-group comparison posttest. The population of this research is all fertile women who experienced leucorrhea with a total sampling technique. It obtained a sample of 30 respondents. The data analysis test is using Chi Square. Results: The results showed p 0.006 (<0.05) and the value of OR 1.667 with a confidence interval of 95%. It can be concluded that the H0 is rejected, which means that a sitz bath with Red Betel Leaf (Piper crocatum) is effective in treating leuchorrhea. So, the combination of standard therapy and a sitz bath with Red Betel Leaf (Piper crocatum) on fertile women with leuchorrhea is twice as effective to resolve leuchorrhea. Conclusion: This research is expected to show that a sitz bath of Red Betel Leaf (Piper crocatum) can be used as a complementary therapy to resolve leuchorrhea in fertile women.